Enhancing Individual Resilience At Work: A Qualitative Exploration Of The Millennial Generation - Sri Astuti Nasir (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study explores how millennial employees develop individual resilience in the workplace amid increasing volatility, uncertainty, complexity, and ambiguity. Using a qualitative phenomenological approach, this research involved five millennial workers employed in private companies, selected through purposive sampling based on relevance to the research focus. Data were collected through semi-structured interviews and analyzed using thematic analysis to identify patterns of meaning within participants’ lived experiences. The findings reveal three core themes shaping millennial resilience: (1) resilience as an adaptive capacity that allows individuals to regulate emotions, reinterpret challenges, and respond constructively to organizational changes; (2) organizational support—particularly supportive leadership, psychological safety, opportunities for learning, and flexible work arrangements—as a critical external factor that strengthens resilience; and (3) active engagement as the behavioral manifestation of resilience, reflected through proactive effort, teamwork, and a willingness to contribute beyond formal job roles. The study highlights that resilience is not merely a personal trait but a dynamic process shaped by continuous interaction between individual coping strategies and organizational practices. Millennials interpret workplace challenges not only as stressors but also as opportunities for self-development, provided they operate within a psychologically safe and supportive environment. Practically, the findings underscore the need for organizations to implement development programs focused on psychological resilience, cultivate empathetic and empowering leadership styles, and promote collaborative work cultures that enhance well-being and work engagement. Strengthening resilience among millennial employees is essential for sustaining performance, maintaining adaptability, and ensuring organizational effectiveness in the modern VUCA-dominated workplace.